Food label literacy among Malaysian school adolescents: A prevalence study. - Syaza Kamarudin; Bee Koon Poh; Hanis Mastura Yahya; Norazmir Md Nor; Raduan Sharif; Ruzita Abd Talib (PLoS ONE)
Making informed food choices is crucial for all ages, especially adolescents who are involved in selecting and buying food. Understanding nutrition labels helps guide choices and ensures nutritional needs are met. This study aims to assess the prevalence and level of food label literacy among school-going adolescents aged 13-16 in Malaysia. This study involved a cross-sectional online survey and was sampled by random sampling involving secondary school adolescents aged 13-16, totaling 1983 subjects across five regions in Malaysia: Central, Southern, Northern, and East Coast of Peninsular Malaysia, as well as East Malaysia (Sabah and Sarawak). The questionnaire includes sections on sociodemographic and anthropometric information, as well as three main food label literacy domains: comprehension and interpretation of food labels, skills in using food labels, and attitudes towards food labels. A total of 89.7% of adolescents read food labels with a moderate level of literacy across all three domains (comprehension and interpretation, skills in usage, and attitudes) classified using predefined score ranges based on previous studies. A significant relationship (p < 0.05) was found between age and body mass index-for-age z-score (BAZ) with the level of food label literacy, indicating higher literacy values in older adolescents. Mean scores of all domains A, B, and C across the five regions indicated significant differences at F(4,1978) = 25.8, p = 0.000, F(4,1978) = 17.43, p = 0.000, and F(4,1978) = 25.20, p = 0.000. In conclusion, the proportion of Malaysian adolescents reading food labels is high (89.7%). Nevertheless, the food label literacy level across all three domains is moderate. Hence, the promotion of the importance of nutrition labels in schools through organised programs such as interactive hands-on label reading activities and school-based nutrition campaigns are recommended. A crucial gap in health education can be addressed by fostering proper comprehension, skills, and attitudes toward food labels and facilitating informed dietary practices among adolescents.